S3_5 Attack of the Aliens - Kamran, Aneesah; Rhodes, Kira; Doherty, Lauren (Physics Special Topics, 2017)
Modelled after a very famous scene in the film Alien (1979), we calculated the force required by a “chestburster” alien to break through a human chest cavity in one blow. We found this force to be 155000 N. We also calculated that the speed at which the alien would need to leave the body would be 102 m/s.